A density functional theory and grand canonical Monte Carlo simulations study the hydrogen storage on the Li-decorated net-τ. (18th June 2021) - Shi, Mingmin; Wu, Qiang; Huang, Xin; Meng, Zhaoshun; Wang, Yunhui; Yang, Zhihong; Hu, Jing; Xu, Yi; Zhao, Huaihong; Yan, Gang
Abstract: To find ideal hydrogen storage media, hydrogen storage performance of Li decorated net-τ has been investigated by first-principles calculations. Maximum 6 Li atoms are adsorbed on net-τ, with the average binding energy of 2.15 eV for per Li atom. Based on 6Li-decorated net-τ, up to twenty H2 molecules are adsorbed, with a high H2 storage capacity of 12.52 wt% and an appropriate adsorption energy of 0.21 eV/H2 . Finally, H2 uptake performance is measured by GCMC simulations. Our results suggest that Li-decorated net-τ may be a promising hydrogen storage medium under realistic conditions. Graphical abstract: Image 1 Highlights: Net-τ was proposed to examine the capacity of hydrogen storage. The H2 storage gravimetric density of 12.52 wt% can be obtained by DFT calculations. GCMC simulations also addressed high H2 uptake capacity.